A new micro‐forceps for endoscopic ultrasound‐guided through‐the‐needle biopsy in the diagnosis of pancreatic cystic lesions: Single center experience. Issue 9 (13th August 2021) - Stigliano, Serena; Covotta, Francesco; Di Matteo, Francesco M
Abstract: Background and Aim: Endoscopic ultrasound (EUS)‐guided through‐the‐needle biopsy (TTNB) has improved the diagnostic algorithm of pancreatic cystic neoplasms (PCNs). Recently, a new through‐the‐needle micro‐forceps device (Micro Bite, MTW Endoskopie Manufakture) has been introduced. The primary aim was to assess the safety and technical success of this new type of micro‐forceps. The secondary aim was to evaluate the diagnostic role of EUS‐TTNB. Methods: Retrospective study of consecutive patients receiving EUS‐TTNB for the diagnosis of PCNs. Two micro‐forceps were used: Moray Micro‐forceps and Micro‐Bite. Cystic fluid was collected for cytological analysis. Categorical variables were analyzed by Fisher's exact test, and continuous variables were analyzed by Student's t ‐test. P  < 0.05 was considered significant. Results: Forty‐nine patients enrolled in the study (24% male; mean age 63 ± 14 years). TTNB was successfully performed in all patients. A diagnostic sample was obtained in 67.3% PCNs with TTNB compared with 36.7% with cyst fluid cytology ( P 0.01). Adverse events rate was 10.2% and occurred in older patients (76.6 ± 5.4 vs 61.3 ± 13.7 P = 0.02). The 51% underwent EUS‐TTNB with Micro Bite. A diagnostic sample was obtained in 52% PCNs with Micro Bite compared with 24% obtained with cyst fluid cytology ( P = 0.07). Comparing the two devices, the rate of diagnostic sample obtained with the micro‐forceps Moray was higher than that obtained with the Micro Bite (20/24 [83.3%] vs 13/25 [52%] P 0.03). Conclusions: EUS‐TTNB increases the diagnostic yield of PCNs. The new Micro‐Bite could represent a valid alternative to the currently used Moray Micro‐forceps, but its diagnostic rate is still suboptimal and further studies are needed. Abstract : Endoscopic ultrasound (EUS)‐fine needle aspiration (FNA)‐based cytology has low sensitivity and specificity to differentiate pancreatic cystic neoplasm (PCN). EUS through‐the‐needle micro‐forceps (EUS through‐the‐needle biopsy [TTNB]) increases the diagnostic yield. A new EUS‐TTNB microforceps device (Micro Bite, MTW Endoskopie Manufakture) has been introduced, which was successfully performed in all 49 patients. Fifty‐one percent of the patients underwent EUS‐TTNB with MTW, and technical success was 100%. A diagnostic sample was obtained in 52% of PCNs with Micro Bite compared with 24% obtained with cyst fluid cytology ( P  = 0.07). Overall EUS‐TTNB diagnostic rate was greater than FNA (67.3% vs 36.7% P  < 0.01). This is the first study evaluating the efficacy of the MTW in the diagnosis of PCN. MTW represents a valid and safe alternative to the Moray micro‐forceps. High diagnostic yield of EUS‐TTNB was obtained in pancreatic cystic neoplasm.